2010
DOI: 10.1093/imammb/dqq010
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-rich plankton communities stabilized via predator-prey interactions: revisiting the role of vertical heterogeneity

Abstract: Self-regulation of population dynamics in nutrient-rich (eutrophic) ecosystems has been a fascinating topic for decades in ecological literature. Simple theoretical models predict population oscillations of large amplitudes in such systems, those predictions often being at odds with reality. Plankton communities possess a particular combination of two important properties, making them unique among ecosystems with eutrophication. These are: (i) the existence of a pronounced spatial gradient of the prey growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 51 publications
2
37
0
1
Order By: Relevance
“…Assuming that copepods forage through chemodetection stabilizes the dynamics so that the system tended to the persistence stable steady state (Figure 1c) across the full range of K. These results are consistent with [27], who showed infochemical-mediated predation to be stabilizing, and Morozov et al (2011) [32], who showed vertical heterogeneity to have a stabilizing effect of the system dynamics, even at an unlimited nutrient load.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Assuming that copepods forage through chemodetection stabilizes the dynamics so that the system tended to the persistence stable steady state (Figure 1c) across the full range of K. These results are consistent with [27], who showed infochemical-mediated predation to be stabilizing, and Morozov et al (2011) [32], who showed vertical heterogeneity to have a stabilizing effect of the system dynamics, even at an unlimited nutrient load.…”
Section: Discussionsupporting
confidence: 81%
“…It is for this reason that we model copepods in terms of the integral population size over the water column by an ordinary, rather than a partial, differential equation. In particular, copepods exhibit vertical migrations, often migrating between surface and deep layers several times over short time periods of 0.5-2 days [32], making the active movement of copepods a fast process in comparison to the passive diffusion of phytoplankton, microzooplankton and chemicals. It would therefore be incorrect to assign an individual copepod to a fixed horizontal layer in the water column in this model time-scale [32].…”
Section: The Modelmentioning
confidence: 99%
“…The spatial asymmetry in biomass distribution is analogous to the coupling of fast and slow energy channels by consumers reported for various systems (Rooney et al 2006), such as link between pelagic and benthic areas of lakes by fishes (Schindler and Scheuerell 2002), connected lakes (Griffiths et al 2013), or soil food webs (Moore et al 2004). The two channels display differences in productivities due to traits of organisms (Abrams et al 2012) or environmental variations (e.g., gradients in the water column; Morozov et al 2011), which can produce asynchronous dynamics. The stability results from the rapid foraging of the predator shifting between two energy channels (Rooney et al 2006) or from the preference of the consumer for the slow energy channel (Blanchard et al 2010).…”
Section: Consumer Spatial Flows and The Nutrient Storage Mechanismmentioning
confidence: 99%
“…Modelling predator-prey interaction in a spatially heterogeneous habitat, where an exact location of individuals on a demographic timescale cannot be properly assigned, requires the implementation of partial integro-differential equations. However, the complexity of this framework makes it rather difficult to treat the model analytically: all previous findings have been obtained by direct numerical simulations of the equations for particular parameterisations of the model ingredients [30,27]. This, obviously, cannot be considered as a rigorous proof of stabilization of the system.…”
Section: Introductionmentioning
confidence: 99%